Scrutinizing Activities in Online Extensive Reading Classroom: Highlighting Students’ Voice - Asri Siti Fatimah; Neni Marlina; Nita Sari Narulita Dewi (AL-ISHLAH: Jurnal Pendidikan, 2022)
Activities of reading numerous easy texts known as Extensive reading have successfully proven in building the students’ reading motivation and interest. Different from intensive reading which forces students to comprehend all of the words in the text, this activity is really beneficial to develop a love of reading. In this study, several activities have been conducted in an online extensive reading classroom. Not by giving comprehensive questions like intensive reading, this kind of activity provides interesting classroom activities underlying their general understanding of the text, such as creating reading logs, joining group discussion, giving response on the text, creating creative writing such as making a letter to one of the characters on the story, changing ending/beginning of the story, etc. Thus, this study focuses on scrutinizing classroom activities in an online extensive reading classroom by focusing on investigating the student’s voice. A survey encompassing 149 students was conducted in order to find their perception related to the activities of extensive reading in the virtual classroom. The findings show that most of the students show positive perception on the activities. The use of online platforms such as blogs, WhatsApp, zoom and google classroom also contribute on the students’ enjoyment and engagement. It undoubtedly forces them to be active in the classroom and show their best performance during joining the classroom activities.